Fluorophore core-engineered supramolecular discotic columnar liquid crystals with tunable fluorescent behavior. (20th June 2019) - Mu, Bin; Quan, Xuhong; Zhao, Yu; Li, Xun; Tian, Wei
Abstract : Tunable fluorescent behaviour was achieved for hydrogen-bonded supramolecular discotic columnar liquid crystals via a fluorophore core engineered approach. Abstract : Achieving hydrogen-bonded supramolecular discotic columnar liquid crystals with tunable fluorescent behavior, especially in the solid state, is still a substantial challenge due to the absence of suitable fluorophore components. To this end, we herein report a function-directing expansion based on a C 3 -symmetric tris(imidazole-2-yl)benzene skeletal structure to obtain various fluorophore cores, which are either fused with π-expanded benzene or naphthalene rings, or substituted with tolyl groups twisted out of the core plane. By means of complementary hydrogen-bonding interactions with alkylated benzoic acids, well-organized supramolecular discotic columnar liquid crystals can be formed and readily aligned in a homeotropic fashion. Efficient color-tunable fluorescent behavior, ranging from blue, cyan, green to yellow emission, is achieved with these liquid crystals even in the solid state, which manifest a close correlation with the different structural parameters shown by each of the designed cores, and also the assembled structures of the resultant complexes. Our study will lead to the design of new functional supramolecular liquid crystals that can potentially be applicable as anisotropic optoelectronic materials.